Identification and control the causal agent of root rot disease of cucumber in Iraq - Hussein, Safaa Neamat (Journal of agricultural, environmental and veterinary sciences, 2019)
This study aimed to isolate the causal agent of the root rot disease of cucumber and control it biologically. Samples were collected in the cucumber fields in the Diyala and Saladin governorates of Iraq. Isolation test demonstrated associate fungi belong to the twelve geniuses. Fusarium solani exhibited highly percentage of appearance of 82.15% with frequency 54.00%. Seventy-seven isolates identified as F. solani according to their cultural and morphological characteristics while sixty-five isolates of them amplified successfully with specific primer of Fusarium spp using PCR technique. Isolate DF13 was most virulent isolated while exhibited 0% cucumber seed germination in vitro. The bio-agent Bacillus pumilus demonstrated significant inhibition ability against the fungal isolate DF13 in vitro of 100%. Under greenhouse condition B. pumilus decreased the disease incidence and severity to 30.55% and 20.75% respectively compared to the negative control which was 80.50%, 55.00% respectively.